ANALISIS IMPLIKASI TEORI BELAJAR DALAM PEMANFAATAN VIDEO SEBAGAI STIMULUS PADA PEMBELAJARAN SOSIOLOGI DI UPT SMAN 7 SINJAI - Fajriani Asdar; Farida Febriati; Saheria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to explore the implications of learning theories through the use of video as a stimulus in Sociology learning at UPT SMAN 7 Sinjai. Using a descriptive qualitative approach, this research observes instructional dynamics and student responses to digital media. The results indicate that video effectively visualizes abstract social phenomena, facilitates memory retention through Dual Coding Theory, and reduces students' cognitive load. From a behaviorist perspective, the use of video accompanied by positive reinforcement in the form of teacher appreciation increases active participation. Constructivistically, video acts as a catalyst for peer discussion, allowing students to build understanding collaboratively. Furthermore, the teacher's humanistic approach in considering emotional aspects creates a conducive learning environment. It is concluded that the integration of video as a stimulus—aligned with various learning theories—shifts the learning paradigm toward a student-centered approach while enhancing student motivation and conceptual understanding in Sociology.